OC-008 Stratification of patients with alcoholic hepatitis by analysis of trajectory of serum bilirubin concentration. (17th June 2017) - Parker, R; Cabezas, J; Altamirano, J; Sinha, A; Dhanda, A; Arrese, M; Abad, JP; Vargas, V; McCune, CA; Bataller, R; Holt, A
Abstract : Introduction: Acute alcoholic hepatitis (AAH) has a poor prognosis. We analysed the trajectory of serum bilirubin concentration to stratify patients in terms of risk of morbidity and mortality, and to identify patients who might benefit from corticosteroid treatment. Method: Bilirubin concentration up to 28 days from admission was evaluated in 262 patients with AAH who did not receive steroids at Queen Elizabeth Hospital, Birmingham and Bristol Royal Infirmary, Bristol. Traj software was used to identify distinct bilirubin trajectories. Survival was evaluated with Kaplan Meier and Cox proportional analyses. Findings were validated in a cohort of 74 patients drawn from the UK, USA, Spain and Chile. Finally the utility of using bilirubin trajectory to identify patients who benefited from corticosteroid therapy was evaluated. Results: Three discrete trajectories of bilirubin concentration were identified over 28 days: group 1 'fast fallers', group 2 'static' and group 3 'rapid risers' (figure 1). The course of bilirubin trajectory could be discerned accurately in the first 7 days of admission (Kappa 0.83), allowing for stratification of patients early in their illness. Group 3 had an increased risk of death at 90 days after admission (log rank p<0.001) which remained significant in multivariate analysis (HR of death, 2.88, 1.53–5.42, p=0.001). Rapid risers also demonstrated greater incidence of renal failure (Chi squared p=0.011). ROC analysis showed that categorisation by bilirubin trajectory was comparable to DF and GAHS for prediction of death at 28 days and 90 days after admission. These findings were confirmed in the validation cohort. Finally, examination of patients treated with corticosteroids demonstrated that patients with rapidly rising bilirubin gained the most from treatment with corticosteroids (log rank, group 1 p=0.627, group 2 p=0.540, group 3 p=0.039). Analysis of bilirubin trajectory identified fewer patients who might be eligible for corticosteroid therapy than the discriminant function (25% vs. 88%) but without any loss of efficacy. Conclusion: Identification of types of bilirubin trajectory in alcoholic hepatitis stratifies patients into distinct groups with differing clinical outcomes. This allows accurate identification of a subgroup of patients who benefit from corticosteroid therapy. Disclosure of Interest: None Declared